Ostracism drives group moralization and extreme group behavior. Issue 5 (3rd September 2019) - Pfundmair, Michaela; Wetherell, Geoffrey
ABSTRACT: Sharing beliefs, particularly moral beliefs, is a way to establish social connections. We hypothesized that ostracism leads people who are high in the need to belong to adhere to the moral beliefs of an ingroup, and that moralizing the beliefs of one's group increases the willingness to endorse extreme behavior on behalf of the group. Across two studies, participants were ostracized or included, rated the moral relevance of their group values, and indicated their endorsement of extreme behavior on behalf of the group. Across studies, ostracism increased group moralization in participants high in the need to belong. In Study 2, group moralization translated into endorsement of extreme behavior. Our findings suggest that morality serves a binding function that may be channeled into extreme behaviors. (120 words)